An Interview with Chip Morrison: Public Service as a Value - Morrison, Chip (Maine Policy Review, 1994)
Earlier this year, Charles "Chip" Morrison completed seven years of service in the administration of Maine Governor John McKernan, first as Commissioner of Administration and then as Commissioner of Labor. At a time when experience in government, whether in an appointive or elected capacity, is looked upon by many with a mixture of suspicion and disdain, Morrison preaches the sermon of government-as-service. In this interview, Morrison also talks about the values which have guided him in his public service career and touches upon a number of public policy issues with which he was involved as a department head.
Keywords: Maine; public service; state government